Three Generations of Minahasan Migration to the Netherlands-an Economic (Migration) Study - Pingkan Luciawati Sompi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The The aim of this study is to examine the migration pattern of the Minahasa people to the Netherlands over three generations, focusing on the economic aspect that became one of the main drivers of migration. This research uses a qualitative approach with descriptive analysis that combines historical data, interviews and literature studies related to the migration phenomenon that occurred from the early 20th century to the present. The three generations of Minahasa migration to the Netherlands include: (1) the first generation that left during the colonial period, generally driven by employment factors and the role of the Netherlands as a colonial state, (2) the second generation that began to migrate in post-independence Indonesia, where economic and educational factors were the main considerations, and (3) the third generation that migrated with more diverse motivations, including the search for better economic opportunities and family reasons. The research found that economic migration was a very important factor in each generational phase, although personal motivations and socio-political developments in Indonesia and the Netherlands also played an important role. The impact of this migration is not only visible at the individual level, but also affects social and economic changes in both countries, both in terms of the integration of the Minahasa community in the Netherlands and their contribution to the economic development of the Netherlands. In addition, this study also highlights the differences in migration characteristics from generation to generation.The reasons for the Minahasa migrated to the Netherlands from the first generation to the present are as follows: (1) KNIL were soldiers of the Dutch East Indies Kingdom, some former KNIL soldiers from Minahasa chose to fly and migrate to the Netherlands. The interaction of culture, religion and language that lasted for a long time eventually gave birth to emotional closeness between immigrants, in this case the Dutch and the Minahasa. (2) The Netherlands and the Minahasa are closely related because Minahasa is the 12th province of the Netherlands. This made people loyal to Twapro choose to migrate to the Netherlands. (3) On Santa Claus (a celebration of Christmas welcoming day, which is celebrated by the Dutch and Minahasa residents), on December 5, 1957, the Indonesian government carried out a massive nationalization of assets belonging to the Netherlands, the embassy and consulate (Netherlands) was closed, and evacuation plans were prepared everywhere (massive expulsion of Dutch citizens out of Indonesia). At that time, not only Dutch citizens were forcibly evicted, but also many Minahasa people who migrated to the Netherlands on their own wishes and choices by boarding Dutch ships together to the Netherlands. (4) A movement involving Minahasa people occurred in 1958 which was Permesta. For a just and prosperous economy as well for a life that is safe, comfortable and peaceful. (5) The creation of the Jakarta Charter, which was signed on June 22, 1945. At this time, gradually, the Minahasa people migrated to the Netherlands because they were worried about their religion as a minority in their country. (6) Many Minahasa people have been displaced, as a result of the